(untitled) (Journal of Asian Development Studies, 2025)
Due to upcoming legislation promoting internal and external audits, the AI ethics and governance auditing ecosystem has grown rapidly in recent years. AI-enabled technology abuse in the accounting sector has created new ethical difficulties for professional accountants. In this digital age, accounting ethics are crucial. However, this changing terrain is little understood. AI’s use in auditing creates ethical problems, which this study examines by examining how well it respects the five IESBA principles. In a qualitative research, auditors utilized semi structured interviews to explore AI adoption difficulties and solutions at several organizations. According to the data, AI is currently utilized for routine and administrative tasks, but its effect will rise. The auditing industry will need greater technological expertise and higher ethical standards. Being excessively reliant on automated systems, algorithmic biases, and lack of transparency in AI decision-making are ethical concerns. To address these difficulties, auditing firms are emphasizing human judgment and supervision and offering targeted training. The ethical analysis and professional replies are guided by Rest’s Four-Component Model. The study provides practical advice for auditors, organizations, and politicians who wish to effectively integrate AI to retain trust, accountability, and professional integrity in the ever-changing audit environment.